Absenteeism, unemployment and employment protection legislation: Evidence from Italy - Vincenzo Scoppa; Daniela Vuri (IZA Journal of Labor Economics, 2014)
Efficiency wages theories argue that the threat of firing, coupled with a high unemployment rate, is a mechanism that discourages employee shirking in asymmetric information contexts. Our empirical analysis aims to test the role of unemployment as a worker discipline device, considering the different degree of job security offered by the Italian Employment Protection Legislation to workers employed in small and large firms. Controlling for a number of individual and firm characteristics, we investigate the relationship between worker's absences which act as a proxy for employee shirking and local unemployment rate (at the provincial level). We find a strong negative association between unemployment and absenteeism rate, larger in magnitude in small firms due presumably to a significantly lower protection from dismissals in these firms. As an indirect test of the role of unemployment as worker discipline device, we show that public sector employees, almost impossible to fire, do not react to the local unemployment.
Keywords: J41; M51; J45; 330; Shirking; Absenteeism; Employment protection legislation; Unemployment